Association between interleukin-6, C-reactive protein and adiponectin with adiposity: Findings from the 1993 pelotas (Brazil) birth cohort at 18 and 22 years. (October 2018) - Menezes, Ana Maria Baptista; Oliveira, Paula Duarte; Wehrmeister, Fernando César; Gonçalves, Helen; Assunção, Maria Cecilia F.; Tovo-Rodrigues, Luciana; Ferreira, Gustavo Dias; Oliveira, Isabel O.
Highlights: There is a positive association between IL and 6 and CRP with body adiposity. The analysis between adiponectin and adiposity shows an inverse association. These associations are both cross-sectional and prospective and cumulative. Women show higher mean IL-6, CRP and adiponectin when compared with men. The associations were found in a cohort at 18 and 22 years of age and in both sexes. Abstract: Background: Most of the literature has shown a direct association between adiposity, interleukin-6 (IL-6) and C-reactive protein (CRP), and an inverse association with adiponectin. The aim of this paper was to assess the association of obesity measurements and IL-6, CRP and adiponectin. Methods: We performed cross-sectional/longitudinal analysis in the 1993 Birth Cohort in Brazil. Associations between IL-6 (pg/mL), CRP (mg/L) and adiponectin (µg/Ml) with body mass index (BMI), waist circumference (WC), percentage total fat mass (FM) (BODPOD) and trunk FM (DXA) were verified. Four trajectory variables were generated: (a) highest tertile/obesity according to BMI in both follow-ups; (b) highest tertile/obesity only at 18 years; (c) highest tertile/obesity only at 22 years; (d) not in the highest tertile/not obese at both ages. Results: We found a direct association for IL-6 and CRP and an inverse association for adiponectin with measures of adiposity. For instance, for females, the highest mean IL-6 and CRP, respectively, was for those who had been in the obese category at 18–22 years (2.49; 3.75), in the highest tertile of WC (2.11; 3.08), in the highest % of FM (1.56; 3.30 l), and in the highest tertile of trunk FM (2.07; 3.26) (p < 0.001 for all these results in the adjusted analysis). Adiponectin showed an inverse association for the above variables, with lower mean values for males than females. Conclusion: There was a longitudinal and direct association between adiposity and IL-6 and CRP, and an inverse association with adiponectin at 22 years.